(untitled) (Research, Society and Development, 2021)
Spinocerebellar ataxia type 3, also known as Machado-Joseph disease, is an autosomal dominant neurodegenerative disorder, caused by an expansion of the CAG repeat that encodes glutamine in the ATXN3 gene. It affects both men and women, with symptoms that are usually late, appearing around the second decade of life and worsening with advancing age. Although rare, it is the most common form of spinocerebellar ataxia and there is no evidence of therapies capable of promoting a cure. Thus, the present study gathered information to update knowledge about this disease. This is an integrative literature review carried out in the PUBMED, SciELO and BVS databases. Progressive cerebellar ataxia is common in these patients. In the clinical spectrum it includes oculomotor abnormalities, sleep disorders, pyramidal syndrome, extrapyramidal signs and peripheral neuropathy. These neurological symptoms are expressed by the effect of neuronal loss in specific regions of the cerebellum, basal ganglia, brain stem and spinal cord. Anxiety, depression and a high level of fatigue can occur. There is still no effective treatment that can change the natural course of this disease. The most recent studies have the therapeutic target of gene silencing and the interception of toxic effects caused by the proteins produced. Symptomatic therapies and physical therapy have been performed to improve quality of life. Knowing the clinical characteristics of Machado-Joseph disease, which is a serious, incurable, highly debilitating condition and capable of generating a high burden of suffering in its patients, is important in the performance of the neurologist.